Amylin in the Periphery. (2003) - Wookey, Peter J.; Xuereb, Loredanna; Tikellis, Christos; Cooper, Mark E.
Abstract : Amylin (islet amyloid polypeptide) is a peptide synthesized principally in the b-cells of the pancreatic islets together with insulin and has actions as a hormone, growth factor, and modifier of behavior. As a hormone, amylin acts to modify gastric motility, renal resorption, and has metabolic actions. It is postulated that the principal function of amylin as a hormone is the activation of physiological processes associated with feeding. As a growth factor, amylin acts on bone cells, renal proximal tubular cells, and islet b-cells. Amylin has important targets in the brain that mediate its actions in the modification of behavior, including thirst and satiety. In man, amylin can form islet amyloid deposits, an event linked to the reduction of b-cell mass and loss of signal-secretion coupling. Recent evidence has defined a new role for monomeric amylin as a growth factor and regulator of b-cell mass that is postulated to be a key factor in pathophysiological processes that result in overt diabetes.